Identification of Misconceptions on Buffer Material Using Three-Tier Test in the Learning of Multiple Representation (Universitas Negeri Semarang, 2018)
This research was a mixed method with the design of sequential explanatory strategy. This research aims to identify student misconception on buffer solution material and obtain student response to multiple representation-chemoentrepreneurship (entrepreneurship in the chemistry field) teaching materials. Research subjects were 114 students from grade XI MIPA 3, XI MIPA 4, and XI MIPA 5 SMA Negeri 12 Semarang academic year 2017/2018. Three-tier multiple choice diagnostic test obtained from the research data amounted to 20 items, questionnaire to know the student's response to teaching materials, and interview to confirm student's answer. The result of the validation of teaching materials by three validators shows that the teaching materials of multiple representation-chemoentrepreneurship are very suitable to be used in chemistry learning with an average score of 190.33 from 212. The average score of the questionnaire is 28,026 with proper category and reliability of 0.906. The misconception profile obtained is the definition and the properties of the buffer solution 3.421%; the components of buffer solution 2.149%; working principle 2.632%; pH of buffer solution 3.596%; and the role of buffer solution 0.965% with a total misconception 12.763%.